Practicum report presented during the in service training station at FAC Muños, Nueva Ecija and Binuangan Obando, Bulacan. - Dalina, Josephine C. (College of Fisheries, University of the Philippines in the Visayas, 1980)
Fisheries is an applied science, therefore it is imperative or a fishery student to undergo a period of apprenticeship or practicum. The practicum is required to expose the students to practical skills different procedures and management techniques in aquaculture. This paper presents my one-month training at FAC, Nueva Ecija from 27th of April 1979 with special emphasis on cage and rice-fish culture. The work during the prescribed period was conducted from eight too twelve in the morning and one to five in the afternoon, from Monday through Saturday. My remaining months were spent at brackish water fishpond in Binuangan, Obando, Bulacan a private fishpond owned by Mr. Modesto Cruz. During my practice, I undertook major activities as maintenance and management of the pond. Not only did I learned the different procedures in growing fish but also I learned the principles of salt making. My practicum therefore, gave me enough experience, in sights and overall view that inland fisheries are a very qualitative field of science. I believe that activities, which I undertook, were enough for me to face and tackle office work as well as field work in fishpond management being my major course of study.